ANALISIS DAN PERANCANGAN CUSTOMER RELATIONSHIP MANAGEMENT PADA SIKLUS PENDAPATAN BISNIS ONLINE ANNEUI SHOP UNTUK MENINGKATKAN LOYALITAS KONSUMEN - Della Damara; Adhicipta Raharja Wirawan (Perpustakaan Universitas Surabaya, 2018)
The e-commerce’s growth is increasing along with seller and buyer growth, who sell and buy through the internet. Online business’s competition which generated by e-commerce’s growth can’t be avoided and be a special concern to the sellers. The sellers are compete to get a buyers and doing effort to maintain the customer loyalty. Some strategies are done with the intention to get buyers attention and dominate the market. The purpose of this study is to analyze the problems of online business related with effort to increase customer loyalty and design a suitable customer relationship management for the business. This qualitative study is towards to Anneui Shop as an online business. The design recommendation of customer relationship management is based on the problems and business condition. Interview, observation, and document analysis are done to obtain data about the problems and business condition. The result of this study to increase the customer loyalty is to advertising, make a promotion and reseller program, increase the business reputation, give the product information, use patent for the brand, and use database to support the business process.